Experiences of registered nurses on communication with Deaf patients at Katutura state hospital, Namibia - Lunza, Simasiku; Nghitanwa, Emma Maano (International Journal of Medicine, 2017)
The purpose of this study was to explore the experience of registered nurses on communication with Deaf patients. Data was collected using an interview guide. Random sampling technique was employed. Data was transcribed and keywords were identified representing the major categories. Data was analysed using a systematic process in order to deduce themes and sub-themes. During data analysis similar ideas or keywords were coded and similar topics were grouped together into categories. The study concluded that registered nurses lack sign language skills hence their communication with Deaf patients is also challenged. It is recommended that registered nurses needs to be provided with the training in sign language at educational institutions and provision of in-service training on sign language should made available for all health care workers. The study also recommends that Deaf people should be trained in sign languages for effective communication when seeking health care.